Uso cíclico de água salina em amendoim associado a Rizóbio - Santos, Max Ferreira dos (2020)
Peanuts (Arachis hypogaea L.) have a prominent role in the economy of many countries. The crop, classified as very sensitive to salinity, has the ability to benefit from symbiosis with nitrogen-fixing bacteria, reducing the use of synthetic nitrogen fertilizers. Abiotic factors, such as the high concentration of salts in irrigation water, can interfere with the establishment of biological nitrogen fixation (BNF), impairing the development of plants and microorganisms responsible for BNF. The use of inferior quality water in the phenological stages of greater culture tolerance can be a viable strategy to benefit the development of the plant and the rhizobia. Based on the exposed facts, the objective of the present work was to identify the phenological phase in which irrigation with saline, introduced in the peanut culture, has less impact on the production of FBN and grains. To estimate the impact of salinity on the crop, growth and nodulation parameters, gas exchange and nutrient accumulation in the aerial part of peanut plants inoculated and not inoculated with a mixture of rhizobia, subjected to irrigation with saline water (5.0 dS.m-1) at different phenological stages of the culture. The results indicate that the phenological phase in which the salt stress was applied interfered in the efficiency of the FBN, the earlier the stress, the lower the FBN, irrigation with saline water at 46 DAS (in the grain filling phase) had less impact Na grain production, regardless of inoculation with selected strains, native rhizobial strains proved to be efficient in FBN, even without increasing their population (through inoculation with reference strains, as was done for SEMIA 6144 and 630 strains), they were able to nodulate and carry out FBN, showing the need for a program for the selection of native strains to be used as native inoculants.